Primary hyperparathyroidism: Achanging scenario in India - Sangeeta Jha; Muthukrishnan Jayaraman; Aman Jha; Ratan Jha; Kirtikumar D Modi; Jayant V Kelwadee (Indian Journal of Endocrinology and Metabolism, 2016)
Introduction: Primary hyperparathyroidism (PHPT) is largely a symptomaticdisease with varied systemic manifestations, complicated by coexisting Vitamin D(Vit D) deficiency. Increasing awareness, developments in diagnostics, and Vit D supplementation may have an impact on the disease profile of PHPT. Methods: Clinical, biochemical, and pathological profile of PHPT presenting to a tertiary care center in South India were compared in two groups separated as per the period of presentation (Group A: January 1994–May 2007 - 51 cases and GroupB: June 2007–January 2015 - 59 cases). Results: PHPT has remained a disease of female preponderance with similar age of presentation. It is being diagnosed earlier (mean duration of symptoms prior to diagnosis was 38.7 months in Group A, significantly longer than 26 months in GroupB). Bone pain and metabolic myopathy were the most common presentations (60%) followed by pathological fracture (16%), renal calculi (13%), and pancreatitis (7%). Pathological fractures have become less frequent. Vit D deficiency is still a widespread co-morbidity. Radionuclide scintigraphy is an effective localizing tool, but ultrasound can be an inexpensive and widely available screening modality. Conclusion: PHPT still remains asymptomatic disease of bones and stones, although it is being diagnosed early. Greater awareness, Vit D supplementation, and better diagnostic tools have made it a disease with lesser morbidity and effective cure.